La poesía de Ibn Hāni’ ante los problemas sectariosIbn Hani’s Poetry in the face of Sectarian Problems - Bouzouita Trabelsi, Hasna (Anaquel de Estudios Árabes, 2009)
This study is a new appraisal of the work of Ibn Hani (Seville/Ibira 320/932 – Barca 3627973). From the Shia Ismaili branch, his work was judged in different ways. It was devalued by some and praised by others. Ibn Hani enjoyed such fame and prestige in the Islamic West that was he was even compared to the great classical poet Al-Mutanabbi in the East. This article will show how Ibn Hani´s poetry changed from natural to pompous, and even verged on sacrilege. It went against established norms to the point of being labeled as heretical. The study will also show that Ibn Hani poetical innovation was so extreme that his poems were considered affected and archaic. This negative assessment of his work didn’t disturb the author; on the contrary, he kept achieving important successes for the art of Arabic poetry.